POTENSI PENGEMBANGAN KAWASAN AGROPOLITAN DI KABUPATEN SERANG DENGAN MENGGUNAKAN MODEL WEIGHTED OVERLAY: Potential Development of Agropolitan Area in Serang Regency Using Weighted Overlay Model - Bahasoan, Husen (Uniqbu Journal of Exact Sciences, 2021)
The development of the Agropolitan Area aims to increase the income and welfare of the community through accelerating regional development and increasing the attachment of villages and cities. The purpose of this study was to map and determine the location of the agropolitan area and to analyze the area of ​​the agropolitan area that was feasible to be developed in Serang Regency, Banten. The analysis used is Weighted Overlay Analysis. Areas that have the potential to be used as agropolitan areas are scattered in several sub-districts. The sub-districts that have a very large area used as an agropolitan area are Pabuaran District with an area of ​​356.2 hectares and Cikande District with an area of ​​315.25 hectares.